Deletion of the α subunit of the heterotrimeric Go protein impairs cerebellar cortical development in mice - Cha, Hye Lim (2019)
Go is a member of the pertussis toxin-sensitive Gi/o family. Despite its abundance in the central nervous system, the precise role of Go remains largely unknown compared to other G proteins. In the present study, we explored the functions of Go in the developing cerebellar cortex by deleting its gene, Gnao. We performed a histological analysis with cerebellar sections of adult mice by cresyl violet- and immunostaining. Global deletion of Gnao induced cerebellar hypoplasia, reduced arborization of Purkinje cell dendrites, and atrophied Purkinje cell dendritic spines and the terminal boutons of climbing fibers from the inferior olivary nucleus. These results indicate that Go-mediated signaling pathway regulates maturation of presynaptic parallel fibers from granule cells and climbing fibers during the cerebellar cortical development.